ADSORPTION OF URANIUM SIMULATION WASTE USING BENTONITE:TITANIUM DIOXIDE - Basuki, Kris Tri; Hasnowo, Lutfi Aditya; Jamayanti, Elza (Urania : Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2019)
ADSORPTION OF URANIUM SIMULATION WASTE USING BENTONITE TANIUM DIOXIDE. Bentonite is a clay material of high surface area that have galleries within its structure. Bentonite that is modified with TiO2 will have high adsorption capability. In this study, natural bentonite and bentonite:TiO2 were characterized with FTIR, XRD and BET instruments to determine functional group, basal spacing, and specific surface area. This study also investigates the adsorption of bentonite:TiO2 in various environmental factors, such as pH (pH 1, 3, 5, and 8), contact time (10, 20, 30, 40, 50, 60, 70, 90, and 120 min), and initial uranium concentration (20, 40, 60, 80 ppm), and their influences on adsorption capacity, and determine the kinetics equation and adsorption isotherm. Based on FTIR analysis, a decrease in the band of O-H bond from water molecule was observed, which indicates the presence of TiO2 in bentonite interlayer structure. The XRD characterization of bentonite:TiO2 does not show diffraction peak in 001 plane. This is due to delamination of bentonite interlayer structure. Delamination is caused by the presence of TiO2 in large quantities, thus damaging the bentonite interlayer structure into irregular sheets. Bentonite as sheets will cause the basal spacing to increase and it is anticipated that XRD will find it difficult in detecting the 001 plane at a low 2 theta angle. The surface area of bentonite:TiO2 has increased by 12.04 m2/g. The maximum adsorption capacity of U(VI) took place at pH 5.0 for 70 minutes contact time and uranium concentration of 60 ppm. In this study, the adsorption kinetic and adsorption isotherm are pseudo second-order kinetic and Langmuir isotherm. The kinetic constant and maximum adsorption capacity of bentonite:TiO2 are 0.075 g/mg.min and 5.848 mg/g respectively.Keywords: Bentonite, TiO2, Adsorption, Uranium